2015
DOI: 10.1016/j.kjms.2015.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Different risk factors between reflux symptoms and mucosal injury in gastroesophageal reflux disease

Abstract: Gastroesophageal reflux disease (GERD) is diagnosed based on typical symptoms in clinical practice. It can be divided into two groups using endoscopy: erosive and nonerosive reflux disease (NERD). This study aims to determine the risk factors of reflux symptoms and mucosal injury. This was a two-step case-control study derived from a cohort of 998 individuals having the data of reflux disease questionnaire (RDQ) and endoscopic findings. Those with minor reflux symptoms were excluded. The first step compared sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…However, the therapeutic response is still unsatisfactory especially for those patients with nonacidic reflux or esophageal hypersensitivity. Research on new compounds and identifying the risk factors of GERD would be helpful in the treatment of refractory GERD [91011].…”
Section: Introductionmentioning
confidence: 99%
“…However, the therapeutic response is still unsatisfactory especially for those patients with nonacidic reflux or esophageal hypersensitivity. Research on new compounds and identifying the risk factors of GERD would be helpful in the treatment of refractory GERD [91011].…”
Section: Introductionmentioning
confidence: 99%
“…In the ProGERD study (18) alcohol and tobacco were predictors of severe esophagitis (Los Angeles C and D). In contrast, other studies found no differences between EE and non-EE groups (8,23) . In the present study alcohol and tobacco use was slightly more prevalent in the EE group but it lacks significance, possible due small sentence and underreport.…”
Section: Discussionmentioning
confidence: 73%
“…This finding was consistent with the ProGERD (18) , which evaluated the influence of hypertension, coronary disease, circulatory changes, diabetes, lung and inflammatory diseases in two forms of GERD. Li et al (23) also evaluated the participation of hypertriglyceridemia, hypercholesterolemia, low levels of HDL, high levels of LDL and glycated hemoglobin, and found no statistical difference between the groups. This same study did not consider the use of NSAIDs/ASA as a predictor of EE.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, several other factors have been asserted as causes of heartburn symptoms. Metabolic syndrome or its components- and especially hypertriglyceridemia- have been associated with erosive esophagitis or reflux symptoms respectively[ 34 ]. Zheng et al[ 21 ] found that a dose-dependent smoking was linked to the occurrence of gastroesophageal reflux symptoms with a risk of about 37% risk among women and 53% among men.…”
Section: Pathogenetic Mechanisms Of the Main Risk Factorsmentioning
confidence: 99%